Pengaruh Profitabilitas (ROE), Kebijakan Dividen (DPR), Dan Keputusan Investasi (PER) Terhadap Nilai Perusahaan (PBV) Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Nastiti Rizky Shiyammurti; Tiara Ningsih (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
The purpose of this study is to examine and understand the impact of Profitability (ROE), Dividend Policy (DPR), and Investment Decisions (PER), both partially and simultaneously, on Firm Value (PBV) in banking companies listed on the Indonesia Stock Exchange (IDX) as the population. The sampling technique used is purposive sampling, where samples are selected based on specific criteria according to the researcher's discretion. Based on these criteria, a sample of 10 companies was obtained. This study employs panel data regression analysis with the help of Eviews 12 for data processing. In this study, the ratio used as an indicator to measure the dependent variable of firm value is PBV (Price to Book Value). The results of this study indicate that partially, profitability and investment decisions have a positive and significant effect on firm value, while dividend policy has a positive but not significant effect on firm value. Simultaneously, profitability, dividend policy, and investment decisions have a significant positive effect on firm value.